2023
DOI: 10.54097/ehss.v16i.9583
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Digital Marketing in Brand Promotion

Yuan Qian,
Zhilin Sui,
Detang Wang

Abstract: Digital marketing is an innovative marketing model or means of marketing. With the emergence and development of the Internet and Web 1.0, the concept of digital marketing was first proposed and began to be developed. This research analyzes how to use social media, search engine and brand promotion to implement digital marketing and how these three aspects bring advantages to digital marketing. The necessity of social media to enhance brand value is determined and flexibly meet the diverse needs of consumers. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that providing MSMEs with digital marketing training increases their competitiveness by broadening their market reach, raising their profile in the community, and driving up sales (Raghava Krishna Nenavath, 2021). Furthermore, it has been demonstrated that digital marketing techniques including social media marketing, SEO, and brand promotion can increase the competitiveness of homegrown companies (Ellitan, 2023;Qian et al, 2023). To connect with their target market and establish a strong online presence, MSMEs in Indonesia may thus profit from putting these digital marketing methods into practice.…”
Section: Digital Marketing and Competitivenessmentioning
confidence: 99%
“…It has been demonstrated that providing MSMEs with digital marketing training increases their competitiveness by broadening their market reach, raising their profile in the community, and driving up sales (Raghava Krishna Nenavath, 2021). Furthermore, it has been demonstrated that digital marketing techniques including social media marketing, SEO, and brand promotion can increase the competitiveness of homegrown companies (Ellitan, 2023;Qian et al, 2023). To connect with their target market and establish a strong online presence, MSMEs in Indonesia may thus profit from putting these digital marketing methods into practice.…”
Section: Digital Marketing and Competitivenessmentioning
confidence: 99%